Pengaruh Partisipasi Anggaran, Asimetri Informasi, dan Penekanan Anggaran terhadap Kesenjangan Anggaran Pemerintah Kabupaten Wajo - Tenriwaru Tenriwaru (Universitas Islam Negeri Alauddin Makassar, 2015)
This study aimed to examine the effect of budget participation, information asymmetry and emphasis budget against the budget gap (budgetary slack) in SKPD in Wajo. In this study, samples taken were 85 people from 5 Office of the regional work units (SKPD) which consists of a Team of Local Government Budget (TLGB) involved in the preparation of the budget at the Government SKPD Wajo. Data collected through direct observation and survey obtained by distributing questionnaires to the respondents. This research uses descriptive data analysis of qualitative and quantitative. The results showed that budget participation, information asymmetry and emphasis budget affect the budget gap (budgetary slack). It is shown from the analysis of data through questionnaires and test the hypothesis by using multiple regression. The strongest influence on the budget gap is derived from information asymmetry.